Fibroblast growth factor 23‐Klotho and mineral metabolism in the first year after pediatric kidney transplantation: A single‐center prospective study. (5th December 2022) - Kubota, Mai; Hamasaki, Yuko; Hashimoto, Junya; Aoki, Yujiro; Kawamura, Takeshi; Saito, Akinobu; Yuasa, Rena; Muramatsu, Masaki; Komaba, Hirotaka; Toyoda, Masao; Fukagawa, Masafumi; Shishido, Seichiro; et al.
Abstract: Background: The role of fibroblast growth factor 23 (FGF23) levels in mineral metabolism before and after kidney transplantation in pediatric patients is poorly understood. Methods: We prospectively evaluated 24 patients under 18 years of age (4.5 [3.3–9.8] years) who underwent living kidney transplantation between July 2016 and March 2018, and measured intact FGF23 and serum αKlotho levels, and other parameters of mineral metabolism before and after transplantation (Day 7, 1 and 4 months, and 1 year). Relationships between parameters were examined by linear analysis. Results: FGF23 level was 440.8 [63.4–5916.3] pg/ml pre‐transplant and decreased significantly to 37.1 [16.0–71.5] pg/ml at Day 7 post‐transplant (−91.6%, p  < .001). Thereafter, it remained at normal levels until 1 year. αKlotho level was 785 [568–1292] pg/ml pre‐transplant and remained low at Day 7 and 1 month post‐transplant, with an increasing trend at 4 months. Post‐transplant phosphorus levels were significantly decreased compared with pre‐transplant, with a lowest level of 1.7 [1.3–2.9] mg/dl, −5.7 [−6.8, −3.8] SD at Day 4, followed by gradual recovery. Phosphorus levels and the ratio of tubular maximum phosphate reabsorption were significantly and negatively associated with pre‐transplant FGF23 until 4 months of post‐transplant. Pre‐transplant αKlotho was negatively associated with pre‐transplant FGF23 but not FGF23 or other parameters after transplantation. Conclusion: FGF23 in pediatric kidney transplant patients decreased rapidly after transplantation and associated with post‐transplant hypophosphatemia and increased phosphorus excretion. Post‐transplant αKlotho was low early post‐transplant but tended to increase subsequently. Post‐transplant αKlotho was unaffected by pre‐transplant FGF23 or other factors, suggesting pre‐transplant chronic kidney disease status has no effect.